Chances and Risks of Investing in Selected Segments of the Financial Market - Wojtasińska, Anna (Journal of Finance and Financial Law, 2017)
Financial investments are an important part of household finances. They give an opportunity to ensure them financial prosperity and a sense of security. However, they carry some risks. Investing is the process by which an investor crate a portfolio of financial assets that reflects specific investment objectives, such as maximizing profit and / or minimizing risk. The investment is based on profit. However, investors do not always get the expected result often by badly made investment decisions. Each investor is aware that the higher the expected rate of return, the higher the acceptable investment risk. The main purpose of the article is to show the viability of selected forms of investment in risky instruments and to analyze the profitability of these investments taking into account the level of risk in selected financial market segments – capital, precious metals and the forex market.